La fabrique de la protection - Lionel Laslaz; Agathe Robert-Kérivel; Chloé Vial-Pailler; Camille Noûs (Développement Durable et Territoires)
This article proposes to show how changes in the boundaries, the deletion of nature reserves and the resulting compensation, or their absorption into the heart of a national park, illustrate the construction and mark the process of social acceptance of the latter. In the context of the national nature reserves in the mountains (Haute-Savoie, Savoie, Isère, Hautes-Alpes), uses that are difficult to reconcile lead to a review of the limits or even the very existence of the protection perimeters and reflect the arrangements made with them and with the space by the various decision-makers. A reflection on the notion of contiguity and gateway allows us to think about their different strategies of articulation with areas equipped for tourism, notably ski areas. The ability to circulate in the reserves with more or less constraints also contributes to their acceptance.